Water storage capacity of shrub canopy in the central aridsemiarid region of Argentina (Semiárida, 2018)
Water storage capacity by the vegetation is useful for understanding hydrological processes in aridsemiarid ecosystems. The aim of this study was to determine the capacity of shrub canopy water storage based on structural characteristics and biomass of Chuquiraga erinacea, Larrea divaricate and Condalia microphylla, three dominant shrub species of Caldenal y Monte Occidental, Argentina. The study was conducted in Chacharramendi, La Pampa, located on the semiarid central area of Argentina. Predictive models to estimating the aboveground biomass of the species from measurements of diameter and height of plant in the field were determined. Water storage capacity was measured on whole plants from immersion method. Water storage capacity, expressed in percentage of biomass was determined by difference wet weight (PM) fresh weight (PF). The average canopy diameter as the independent variable provided the best fit for predicting aboveground biomass in the three species studied. Chuquiraga erinacea was the species that showed higher water storage capacity with 38%, followed in decreasing order Larrea divaricata and Condalia microphylla with 26% and 23% respectively. The results show that a significant fraction of rainfall is retained by the dense shrub communities that dominate the site, and returns to the atmosphere by evaporation. The water interception by vegetation is key in the hydrological dynamics of arid environments, where the increase of shrub density is a dynamic and progressive process that affects the productivity of the ecosystems of the region.
Keywords: biomass; water storage; shrub; semiaridarid